Bransfield Basin, Antarctic Peninsula: Not a normal backarc basin - González-Casado, J.M.; Giner Robles, Jorge Luis; López-Martínez, J. (Geological Society of America, 2000)
The Bransfield Basin, a marginal basin located northwest of the Antarctic Peninsula, has been habitually considered as a backarc basin associated with the rollback process that took place along an inactive plate boundary, the South Shetland Trench, where the Antarctic and the Phoenix plates meet. New geophysical and structural data discussed in this paper show that the basin opening is related to a sinistral simple-shear couple between the Scotia and the Antarctic plates, and not to the previously suggested rollback mechanism. The widening of the Bransfield Basin and the lack of trench retreat are causing compression in the South Shetland Islands. Two different neotectonic stress directions, with interchanged stress axes, are found in the area of the South Shetland block. Comisión Interministerial de Ciencia y Tecnología (CICYT) [ANT98-0225 y ANT94-0666] Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub